2016
DOI: 10.1186/s13039-016-0229-9
|View full text |Cite
|
Sign up to set email alerts
|

Ring chromosome 18 in combination with 18q12.1 (DTNA) interstitial microdeletion in a patient with multiple congenital defects

Abstract: BackgroundRing chromosome 18 [r(18)] syndrome represents a relatively rare condition with a complex clinical picture including multiple congenital dysmorphia and varying degrees of mental retardation. The condition is cytogenetically characterized by a complete or mosaic form of ring chromosome 18, with ring formation being usually accompanied by the partial loss of both chromosomal arms. Here we observed a 20-year-old male patient who along with the features typical for r(18) carriers additionally manifested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
(48 reference statements)
0
6
0
1
Order By: Relevance
“…This circRNA is an exonic circRNA and is located on chr18 from 32386182 to 32392077, which is annotated as hsa_circ_0108310 in circBase, and its gene symbol is dystrobrevin alpha (DTNA). This gene encodes a cytoskeleton-interacting membrane protein that is involved in the formation and stability of synapses in the permeability of the blood-brain barrier and may be related to congenital heart malformation (38,39). However, the role of hsa_ circRNA_401955 in cancer has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…This circRNA is an exonic circRNA and is located on chr18 from 32386182 to 32392077, which is annotated as hsa_circ_0108310 in circBase, and its gene symbol is dystrobrevin alpha (DTNA). This gene encodes a cytoskeleton-interacting membrane protein that is involved in the formation and stability of synapses in the permeability of the blood-brain barrier and may be related to congenital heart malformation (38,39). However, the role of hsa_ circRNA_401955 in cancer has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results of the present study showed that the DTNA gene was the seed gene of the functional epigenetic modules, suggesting an important role of this gene in the development of HT. The DTNA gene encodes α‐dystrobrevin, a member of the dystrophin‐associated glycoprotein complex, which has been associated with movement disorders, such as Duchenne muscular dystrophy [31]. Collins et al .…”
Section: Discussionmentioning
confidence: 99%
“…The DTNA gene encodes α-dystrobrevin, a member of the dystrophin-associated glycoprotein complex, which has been associated with movement disorders, such as Duchenne muscular dystrophy [31]. Collins et al demonstrated that the expression level of dystroglycan in the thyroid is regulated by thyroid-stimulating hormone [7].…”
Section: Functional Epigenetic Modules and Cnvmentioning
confidence: 99%
“…Високата разделителна способност на микрочипова-та СГХ я прави основен метод на избор при детекцията на кандидат-районите за гени, отговорни за различни генетични заболявания [1]. В някои случаи с неясна етиология са открити фамилни микроструктурни аберации, предавани в небалансиран вид в поколението.…”
Section: дискусияunclassified